Influence of Microgeometry of Surcafes on the Contact Approach of Elements with a Surface Layer - Polijaniuk, A.; Handzel-Powierża, Z. (Engineering Transactions, 1993)
Effects on the microgeometry of surfaces on the contact approach of steel elements of joints at rest are investigated in the paper. A case of elements -with nominally flat surfaces subjected to quasi-statical load is considered. The results of experiments are presented made with the use of an original. device for studying contact phenomenon, designed and constructed in the Institute of Fundamental Technological Research of PAS (IPPT PAN). It is shown to what extent the contact approach depends on the microgeometry of a surface obtained in the machining process.